ANALYSIS OF THE EFFECT OF MANAGERIAL OWNERSHIP AND FINANCIAL DISTRESS ON THE INTEGRITY OF FINANCIAL STATEMENTS - Aulia Hafiida Ade Yolandra; Nurafni Eltivia; Nur Indah Riwajanti (Universitas Pakuan, 2023)
ABSTRACTThis study aims to analyze the effect of managerial ownership and financial distress on the integrity of financial statements. The data used is secondary data from the financial reports of infrastructure, utilities, and transportation companies listed on the Indonesia Stock Exchange in 2021 of 80 companies with 37 samples. The results of the study show that managerial ownership has no effect on the integrity of financial statements. Conversely, financial distress has a negative and significant effect on the integrity of financial reports. Managerial ownership that is too high can also create conflicts of interest and reduce the transparency of financial reports. Therefore, companies need to regulate the level of managerial ownership in a balanced way to maintain the integrity of financial reports.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh kepemilikan manajerial dan financial distress terhadap integritas laporan keuangan. Data yang digunakan adalah data sekunder dari laporan keuangan perusahaan infrastruktur, utilitas dan transportasi yang terdaftar di Bursa Efek Indonesia tahun 2021 sebanyak 80 perusahaan dengan 37 sampel. Hasil penelitian menunjukkan bahwa kepemilikan manajerial tidak berpengaruh terhadap integritas laporan keuangan. Sebaliknya, financial distress memiliki pengaruh negatif dan signifikan terhadap integritas laporan keuangan. Kepemilikan manajerial yang terlalu tinggi juga dapat menyebabkan konflik kepentingan dan menurunkan transparansi laporan keuangan. Oleh karena itu, perusahaan perlu mengatur tingkat kepemilikan manajerial secara seimbang untuk menjaga integritas laporan keuangan.